Effect of high‐shear mixing by twin‐screw extruder on the dispersion and homogeneity of polyacrylonitrile/carbon nanotube composite solution. Issue 4 (12th June 2015) - Yan, Xuejia; Dong, Hongming; Xiao, Zhiwei; Liu, Yaodong; Liu, Tao; Chae, Han Gi; Kumar, Satish
Abstract : High‐shear mixing experiments using twin‐screw extruder were conducted to study the effect of shearing on carbon nanotube (CNT) dispersion in polyacrylonitrile (PAN) polymer solution. Different types of CNTs (few‐wall carbon nanotube and single‐wall carbon nanotube) were used to prepare composite solution at 0.5 wt% with respect to the PAN polymer through various preparation conditions. The resulting PAN/CNT composite solution was characterized using various techniques including dynamic light scattering, preparative ultracentrifuge method, optical microscopy, solution rheology, and high‐resolution transmission electron microscopy. With increasing the number of extrusion cycle, it was observed that the CNT bundle size was moderately reduced, while solution homogeneity and macroscopic CNT dispersion was significantly improved. POLYM. COMPOS., 38:719–726, 2017. © 2015 Society of Plastics Engineers